A randomized, controlled double-blind study comparing the efficacy and safety of dose-ranging voclosporin with placebo in achieving remission in patients with active lupus nephritis - Rovin, Brad H.; Solomons, Neil; Pendergraft, William F.; Dooley, Mary Anne; Tumlin, James; Romero-Diaz, Juanita; Lysenko, Lidia; Navarra, Sandra V.; Huizinga, Robert B.; Adzerikho, Ihar; Mikhailova, Elena; Mitkovskaya, Natalya; et al. (Kidney international, 2019)
Calcineurin inhibitors added to standard-of-care induction therapy for lupus nephritis (LN) may increase complete renal remission (CRR) rates. The AURA-LV study tested the novel calcineurin inhibitor voclosporin for efficacy and safety in active LN. AURA-LV was a Phase 2, multicenter, randomized, double-blind, placebo-controlled trial of two doses of voclosporin (23.7 mg or 39.5 mg, each twice daily) versus placebo in combination with mycophenolate mofetil (2 g/d) and rapidly tapered low-dose oral corticosteroids for induction of remission in LN. The primary endpoint was CRR at 24 weeks; the secondary endpoint was CRR at 48 weeks. Two hundred sixty-five subjects from 79 centers in 20 countries were recruited and randomized to treatment for 48 weeks. CRR at week 24 was achieved by 29 (32.6%) subjects in the low-dose voclosporin group, 24 (27.3%) subjects in the high-dose voclosporin group, and 17 (19.3%) subjects in the placebo group (OR=2.03 for low-dose voclosporin versus placebo). The significantly greater CRR rate in the low-dose voclosporin group persisted at 48 weeks, and CRRs were also significantly more common in the high-dose voclosporin group compared to placebo at 48 weeks. There were more serious adverse events in both voclosporin groups, and more deaths in the low-dose group compared to placebo and high-dose voclosporin groups (11.2%, 1.1%, and 2.3%, respectively). These results suggest that the addition of low-dose voclosporin to mycophenolate mofetil and corticosteroids for induction therapy of active LN results in a superior renal response compared to mycophenolate mofetil and corticosteroids alone, but higher rates of adverse events including death were observed. [Display omitted]